Upaya Optimalisasi Waktu dalam Memperoleh Informasi pada Proses Monitoring Operasional di Departemen Utilitas PT. X dengan Metode DMAIC - Vinces Angelica Gunawan; Jani Rahardjo (Jurnal Titra, 2023)
This study aims to optimize the time required to obtain information in the operational monitoring process of the Utility Department at PT. X, a cigarette production company that has been operating in Surabaya, Indonesia since 1962. Time is a crucial factor that needs to be considered by all industry players, including PT. X. Therefore, PT. X has initiated the implementation of the Industry 4.0 concept to improve time optimization, although it is not yet fully implemented. It is evident that there are still operators who manually input data, and the duration of data collection and processing hampers the optimization by implementing solutions based on identified root causes. After the implementation, there was a significant decrease in the time required for data collection to become information for the Boiler by 96%, Compressor by 96%,and PDAM Water Supply by 97%. Thus, it can be concluded that the implementation of the improvement project is aligned with the company’s objective of achieving time optimization in obtaining information during the operational monitoring process at the Utility Department of PT. X